Compulsive Eating in a Rat Model of Binge Eating Disorder Under Conditioned Fear and Exploration of Neural Mechanisms With c-fos mRNA Expression - Li, Zhi Fei; Chometton, Sandrine; Guèvremont, Geneviève; Timofeeva, Elena; Timofeev, Igor (Frontiers in Neuroscience, 2021)
Compulsive eating is the most obstinate feature of binge eating disorder. In this study, we observed the compulsive eating in our stress-induced binge-like eating rat model using a conflicting test, where sucrose and an aversively conditioned stimulus were presented at the same time. In this conflicting situation, the binge-like eating prone rats (BEPs), compared to the binge-like eating resistant rats (BERs), showed persistent high sucrose intake and inhibited fear response, respectively indicating a deficit in palatability devaluation and stronger anxiolytic response to sucrose in the BEPs. We further analyzed the neuronal activation with c-fos mRNA in situ hybridization. Surprisingly, the sucrose access under conditioned fear did not inhibit the activity of amygdala, instead, it activated the central amygdala. In the BEPs, sucrose reduced the response of the paraventricular hypothalamic nucleus (PVN), while enhancing activities in the lateral hypothalamic area (LHA) to the CS. We found a strong negative correlation between sucrose intake and nucleus accumbens (Acb) activity, and it was reversed by the CS in the BERs. The resistance to devaluating the palatable food in the BEPs could be a result of persistent Acb response to sucrose intake and attenuated recruitment of the medial prefrontal cortex (mPFC). We interpret this finding as that the reward system of the BEPs overcame the homeostasis system and the stress-responding system.